2007
DOI: 10.1097/01.hcr.0000265031.10145.50
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cell Mobilization and Increased Intravascular Nitric Oxide in Patients Undergoing Cardiac Rehabilitation

Abstract: Cardiac rehabilitation in patients receiving stable statin therapy and with low-density lipoprotein cholesterol at goal increases EPC number, EPC survival, and endothelial differentiation potential, associated with increased nitric oxide in the blood. Although this response was observed in most patients, a significant minority showed neither EPC mobilization nor increased nitric oxide in the blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 30 publications
(26 reference statements)
1
59
0
3
Order By: Relevance
“…As pointed out above, several studies clearly demonstrated that an acute bout of exercise either in patients with CAD (2) or healthy subjects (58,86,94) resulted in the mobilization of EPCs from the BM. Along with the mobilization of EPCs, metabolic genes increase transiently after an acute bout and returning to near pre-exercise levels 24 h after the end of exercise (60,61).…”
Section: Single Exercise Bout Vs Exercise Training Programmentioning
confidence: 99%
“…As pointed out above, several studies clearly demonstrated that an acute bout of exercise either in patients with CAD (2) or healthy subjects (58,86,94) resulted in the mobilization of EPCs from the BM. Along with the mobilization of EPCs, metabolic genes increase transiently after an acute bout and returning to near pre-exercise levels 24 h after the end of exercise (60,61).…”
Section: Single Exercise Bout Vs Exercise Training Programmentioning
confidence: 99%
“…I programmi di esercizio fisico controllati e prolungati nel tempo si sono anch'essi dimostrati efficaci nel determinare un aumento delle CEP sia nei soggetti sani che nei pazienti con malattia vascolare [14,24]. I meccanismi alla base di questa mobilizzazione sembrano diversi da quelli visti per il singolo episodio di esercizio fisico massimale.…”
Section: Attività Fisicaunclassified
“…Risultati incoraggianti sono stati ottenuti da programmi controllati di riabilitazione cardiologica applicati su pazienti con pregresso infarto del miocar-dio, sia trattati chirurgicamente che con angioplastica coronarica [31,24].…”
Section: Attività Fisicaunclassified
See 1 more Smart Citation
“…In 35 out of 46 patients with CAD, EPCs and EPC colony-forming units increased after a cardiac rehabilitation program and treatment for 1 month with statin compared with before the program and therapy, but the remaining 11 patients had no increase in either measure; those patients whose EPCs increased from baseline showed increases in plasma nitrite and decreases in annexin-V staining, a marker of apoptosis, in EPCs; over the course of the program, EPCs increased before the nitrite increase in the blood. 101 Most, but not all, patients responded to the cardiac rehabilitation and statin therapy with increases in EPC number, EPC survival, and endothelial differentiation potential, possibly associated with increased NO in the blood. In patients with established CAD, abrupt discontinuation of simvastatin treatment led to a rebound of serum total cholesterol and low-density lipoprotein (LDL) cholesterol levels and decreased endothelial dependent flow-mediated dilatation of the brachial artery; in human umbilical vein endothelial cells, the NO production and eNOS expression were decreased after stopping statin treatment.…”
Section: -Hydroxy-3-methylglutaryl Coenzymementioning
confidence: 99%